Enterococcus faecalis Readily Adapts Membrane Phospholipid Composition to Environmental and Genetic Perturbation - Woodall, Brittni M.; Harp, John R.; Brewer, William T.; Tague, Eric D.; Campagna, Shawn R.; Fozo, Elizabeth M. (Frontiers in Microbiology, 2021)
The bacterial lipid membrane, consisting both of fatty acid (acyl) tails and polar head groups, responds to changing conditions through alteration of either the acyl tails and/or head groups. This plasticity is critical for cell survival as it allows maintenance of both the protective nature of the membrane as well as functioning membrane protein complexes. Bacteria that live in fatty-acid rich environments, such as those found in the human host, can exploit host fatty acids to synthesize their own membranes, in turn, altering their physiology. Enterococcus faecalis is such an organism that is a commensal of the mammalian intestine where it is exposed to fatty-acid rich bile, as well as a major cause of hospital infections during which it is exposed to serum that contains numerous fatty acids. Within, we employed a targeted approach to detect the most common phospholipid species within the membrane of E. faecalis OG1RF via ultra-high performance liquid chromatography high-resolution mass spectrometry (UPLC-HRMS). We examined not only how the composition responds upon exposure to host fatty acids but also how deletion of genes predicted to synthesize the major polar head groups impacted lipid composition. Regardless of genetic background and differing basal lipid composition, all strains were able to alter their lipid composition upon exposure to individual host fatty acids. Specific gene deletion strains, however, had altered survival to membrane damaging agents. Combined, the enterococcal lipidome is highly resilient in response to both genetic and environmental perturbation, likely contributing to stress survival.